An approach of rock blasting simulation of equivalent blasting dynamic-static action - Hao Zhang; Xueyang Xing; Yiteng Du; Tingchun Li; Jianxin Yu (Underground Space, 2025)
Various blasting methods in underground engineering involve rock-breaking processes in enclosed spaces. A whole process of rock blasting is completed by the combination of blasting waves and explosion gas. The two actions exhibit different blasting fracturing characteristics in different time and spatial stages. In this study, an approach of rock blasting simulation of equivalent blasting dynamic-static action is proposed. A set of model blasting experiments under plane strain conditions are carried out to verify from the aspects of feasibility and reliability. The results show that the new method realizes the effective coupling of blast waves and explosion gas in terms of rock-breaking characteristics and pressure wave characteristics. The blasting effects have a high similarity between the simulation result and experimental result, and the maximum error on the damage range and the peak stress is 4.02% and 8.90%. The rock breaking mechanisms of three blasting methods in underground engineering that affect the blasting waves and explosion gas are discussed. The superiority of the new method is evaluated. When the decoupling coefficient is increased, an optimal decoupling coefficient is discovered, which reflects the consistency between the blasting results and the actual situation. When the confining pressure is increased, the inhibition ability on quasi-static action is obviously stronger than that of blasting dynamic action. In slotting blasting, the quasi-static action is the main contributor in the formation of holes penetration. The simulation results identify the rock breaking contributions between blasting waves and explosion gas well. The new simulation method can provide a reliable tool for understanding of the rock-blasting mechanism and restoring the whole blasting process.